English Language Learners' Access to and Attainment in Postsecondary Education. Issue 1 (21st August 2012) - Kanno, Yasuko; Cromley, Jennifer G.
<x xml:space="preserve">Abstract</x> Although English language learners (ELLs) are currently the fastest‐growing group among the school‐age population in the United States, there is surprisingly little information on their participation in postsecondary education. Using the National Education Longitudinal Study of 1988 (NELS:88), a nationally representative sample of eighth graders who were followed for 12 years, we present one of the first national‐level examinations of ELLs' access to and degree of attainment in postsecondary education. Our analyses show that ELLs lag far behind both English‐proficient linguistic minority students and monolingual English‐speaking students in college access and attainment. Only one in eight ELLs in the NELS:88 study earned a bachelor's degree, whereas one in four English‐proficient linguistic minority students and one in three monolingual English speakers did. In addition, one in five ELLs was a high school dropout. Subsequent probit regressions reveal that a host of nonlinguistic factors, rather than the ELLs' linguistic background per se, contributed to ELLs' limited postsecondary education access and attainment.